POLA PENGASUHAN ORANG TUA MENURUT HUKUM KELUARGA ISLAM DI DESA KONGKOMAS KABUPATEN TOLITOLI - Muzayyanah; Sapruddin; Ruslan, Murniati (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2024)
Parents are responsible for guiding, protecting, caring, educating and directing children at every stage of their development. As a Muslim, it is recommended that this process carried out based on Islamic family law or what is usually called hadhanah. This research aims to see parenting style according to Islamic family law in Kongkomas Village, Basidondo District, Tolitoli Regency. The type of research used is empirical law with data collection techniques in the form of interviews, observation and documentation. The results from 37 families represented by mothers show that the parenting style used by the majority of parents is democratic. The Democratic parenting style places children as a priority while continuing to supervise them. Based on Islamic family law, parents in Kongkomas Village focus on fulfilling their children's physical, emotional and religious education needs.